Knowledge, Attitude and Practices of Cross Infection Control Protocols among Dental Students and Professionals - Sharqa Qasim, Syeda Maryam Fatima, Syeda Alizeh Hassan, Nauman Rauf Khan, Amna Nauman Khan, Sarah Rabbani (Pakistan Journal of Medical & Health Sciences, 2022)
To evaluate dentists’ knowledge, attitude, and practice of cross infection control protocol. The questionnaire proforma was based on 15 questions was used to check the knowledge, attitude, and practice of the standard infection control protocols among the 3rd and 4th-year students of BDS, house officers and demonstrators of College of Dentistry, Sharif Medical and Dental College, Lahore, who were active in dental health provision in a clinical setting. A total of 200 participants were enrolled in the study after convenient sampling. We found that despite good knowledge of safety protocols, implementation of these standards is lacking. Non-compliance in following standard infection control protocols is a big challenge and can increase the risk of cross-infection.